Patterns and determinants of hypertension in Botswana - Keetile, Mpho (Z Gesundh Wiss, 2015)
AIM: This study examines the patterns and determinants of hypertension in Botswana. SUBJECTS AND METHODS: In 2007, a cross-sectional survey of chronic non-communicable diseases and risk factors was conducted by the Ministry of Health and World Health Organisation using the STEPS approach. STEP 1 was the collection of demographic data, STEP 2 was the physical measurement of the height, weight, waist and hips, and blood pressure; STEP 3 was biochemical measurements, which included the collection of blood samples. A nationally representative sample of 4003 individuals aged 25–64 years was included for analysis. RESULTS: From a total sample of 4003 respondents, the national prevalence of hypertension was estimated to be 16.9 % (9.9 % for males versus 18.9 % for females). Logistic regression analysis indicated a positive association between gender and hypertension prevalence, with females (OR 1.9) more likely to be hypertensive. Hypertension increases significantly with age for both males and females. For women a high educational level and employment status were not associated with hypertension. Meanwhile, of all the behavioural risk factors, obesity was the only one with a significant association with hypertension. CONCLUSION: The implications of this study are that a reduction in obesity through a balanced diet and increased physical activity will have far-reaching results in lowering hypertension. Botswana’s health system should place greater emphasis on the detection of hypertension at early ages and create awareness programmes for both the general population and health personnel with respect to the detection, treatment and control of hypertension.